Exogenous spermidine modulates polyamine metabolism and improves stress responsive mechanisms to protect tomato seedlings against salt stress - Raziq, Abdul (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022. Published by Elsevier Masson SAS.